Regional identity and sustainable development in Transylvania: german cultural heritage - Bodocan Voicu; Rusu Raularian; Egresi Istvan; Schreiber Wilfried (Miscellanea Geographica: Regional Studies on Development)
The Transylvanian identity, deeply rooted in the region’s cultural landscape, has been significantly shaped by over eight centuries of German cultural influence within the South-East Carpathians. The number of Germans (Saxons) in Transylvania declined from more than 200,000 in 1930 to less than 10,000 in 2021. Nevertheless, German cultural heritage is still present, especially in southern Transylvania – mostly in Brașov and Sibiu counties, in parts of Alba, Mureș, Hunedoara counties, and in Bistrița and the area around it. This heritage is exemplified by fortified cities and fortresses, fortified churches, religious edifices, and civilian architecture; many of these are recognized internationally by UNESCO; in particular, the historic centre of Sighișoara and six Saxon villages with their fortified churches have been designated as World Heritage Sites. This rich cultural legacy is primarily leveraged through tourism, with Brașov, Sibiu, and Bran Castle ranking among Romania’s top tourist destinations.